Natural Potential and Local Resources of Tourism Villages in Extreme Poverty Alleviation - Daniel Adolf Ohyver; Risman Jaya; Sudarmi; Ismail; Alisyahbana, Andi Naila Quin Azisah (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to explore the natural and local resources that can be utilized as economic assets to alleviate extreme poverty in Kolaka Regency. A qualitative research approach was employed, gathering data through interviews with beach managers, field observations, and documentation. The findings indicate that the area's natural beauty, marine resources, and rich cultural traditions play a critical role in attracting tourists and serving as sustainable economic drivers. These resources not only enhance tourism but also provide opportunities for local communities to develop businesses and improve livelihoods. However, to ensure the continued success of tourism as a poverty alleviation tool, environmental preservation and cultural conservation must be prioritized. This includes implementing eco-friendly tourism practices that protect the natural environment while promoting local traditions. Additionally, collaboration between local communities, the government, and stakeholders is essential to create inclusive and long-term benefits. This research is expected to contribute to formulating effective tourism development strategies that can alleviate extreme poverty and improve the well-being of the local population.